Anti-Paraflagellar Rodc Antibodies Inhibit the In-Vitro Growth of Trypanosoma Brucei Brucei - Mukisa, Ambrose; Aguttu, Claire; Lubega, George W.; Kyambadde, Joseph; Alibu, Vincent P.; Vuzi, Peter C. (American Academic Scientific Research Journal for Engineering, Technology, and Sciences, 2018)
Paraflagellar rod (PFR), a conserved structure expressed in all lifecycle stages of the order kinetoplasida except in the amastigotes is vital for the parasites survival. In T.b.brucei, the PFR protein has two major components, PFRc and PFRa with molecular mass 73kDa and 68kDa respectively. Experimental evidences implicate the PFR protein as a highly immunogenic and protective antigen. However, its immunogenic properties underlying its suitability as vaccine candidate has not been adequately investigated in-vitro. This study aimed to demonstrate the growth inhibitory potential of PFR protein against T.b.brucei parasites in–vitro. Antibodies against a recombinant form of the PFRc protein were produced and used to generate immune response. A deoxyribonucleotide (DNA) segment of approximate 672bp encoding the PFRc protein component was amplified using polymerase chain reaction (PCR), cloned and expressed in E.coli (BL21) cells. A 200 μg portion of the purified PFRc protein mixed with 100μl Freund's complete adjuvant (FCA) was used to immunize rabbits. An antibody titre of 2.5 x 104 reciprocal dilutions was obtained following three immunisation boosts, spaced two weeks apart. Western blot analysis showed that rabbit anti-PFRc antibodies recognised specifically a 25kDa protein corresponding to the estimated size of the expressed PFRc protein. 25% of purified anti-rabbit IgG antibodies were able to inhibit ~70% T.b.brucei parasite in vitro
Keywords: Anti-Paraflagellar rod c; antibodies.; in-vitro growth; Trypanosoma Brucei Brucei